PERENCANAAN DAN PENGEMBANGAN SISTEM DISTRIBUSI AIR BERSIH KECAMATAN SAMARINDA ILIR DAN SAMARINDA SEBERANG KOTAMADYA SAMARINDA - Atiek Moesriati (Purifikasi, 2005)
Development plan of clean water distribution system of Samarinda by PDAM Samarinda is based on the deficiency of clean water service which only 52,15 %. Distribution development is given priority to area served by IPA Selili and IPA Samarinda Seberang. This distribution development was conducted by utilizing Epanet Version 2.0 program. Evaluation was performed based on existing data, survey results from costumers and water pressure at costumer’s meter. To meet water demand until year 2014, additional capacity at 50 liter/second was done to increase becomes 170 L/second. While at IPA Samarinda Seberang, extra capacity at amount of 120 Liter/ second was done to increase becomes 220 Liter/second. Pipe addition on the development planning used PVC pipe, which is in diameter 200 mm with 14.849 m length, diameter 250 mm with 2630 m length, and diameter 300 mm with 3480 m length.